Sejarah Ilmu Balagah, Tokoh dan Objek Kajiannya - Syarif, Maria Ulfah; Amrah, Amrah; Darmawati, Darmawati (IAIN Bone, 2023)
Al-Qur'an is the holy book of Muslims written in Arabic, containing Allah SWT's word,which is a guide for humankind. The existence of Al-Qur'an with a very rich plurality of Arabic vocabulary is concrete evidence of how Al-Qur'anhas incarnated as a holy book that is unrivaled by other books and literary works on this earth.The beautiful arrangement of sentences, the selection of good language, and the placement of a balanced vocabulary emphasize the miracle of Al-Qur'an in its contents, including universal religious information. Hence, it is known worldwide as a book containing instructions for life, hudan lin nÄs, or way of life. It helps reinforce how Islamic religious teachings truly become Rahmatan Lil 'Alamin.Along with the revelation of the Qur'an, various scientific disciplines began to emerge, such as interpretation, hadiá¹¡, nahw, á¹£arf, balÄgah, and other knowledge. The science of balÄgah is a scientific discipline that aims to study Al-Qur'anas an effort to understand and reveal the contents in terms of balÄgahan, thus showing a comparison of the words of balÄgah experts and Hadith Nabawito explain the words of the most mature Apostle of Allah and the words of the Arabs, both poetry and prose. This article examines the history of the development of the Arabic language, specifically covering the matter of the early embryos emerging and the development of the 'science of Balagah' as well as describing the figures who played a role in the history of its development, including the objects that are the focus of the study of the science of Balagah.Â Â